Education and Counseling on Adolescent Reproductive Health in High School - Dadang Muhammad Hasyim; Elvina Triana Putri; Desty Endrawati Subroto; Sulaeman Sulaeman; Habibi Habibi (PT. Global Research Collaboration, 2024)
Reproductive health is an important aspect that adolescents need to understand to maintain their physical and mental well-being. This community service program aims to provide education and counseling about reproductive health to students of IT As-Syakur High School, targeting students aged 16-18 years. The methods used include face-to-face counseling, interactive discussions, simulations, and utilizing digital platforms for self-study. The material presented covers reproductive anatomy, the risks of sexually transmitted diseases (STDs), early pregnancy, contraception, and psychosocial aspects related to relationships and decision-making. The implementation results showed a significant increase in students' understanding after the counseling, with an average improvement from 60% to 85% in the post-test. A total of 90% of students understood reproductive anatomy, while 85% understood the risks of STDs, and 80% mastered the material on contraception. The use of digital media by 65% of students for self-study also demonstrated the program's effectiveness. This program successfully addressed the stigma among students regarding reproductive health and encouraged their active involvement in learning. This success provides a strong foundation for implementing similar programs in the future with a broader scope, involving parents and teachers, and supporting the sustainability of the program through a technology-based approach.